Analisis Pencapaian Indeks Pembangunan Manusia di Indonesia Menggunakan Model Subdistribution Hazard Ratio Berbasis Competing Risk - Anisa Aliyatul Hikmah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
The Human Development Index (HDI) is an important indicator used to measure the level of development and welfare of a community in a region, as it reflects key dimensions such as health, education, and standard of living. In the process of achieving HDI categories, a region may experience several competing events, where the occurrence of one type of event can prevent or alter the probability of another event. This condition requires an analytical approach that is capable of considering the existence of competing events in order to produce more accurate and reliable estimates. This study aims to apply the Fine-Gray Subdistribution Hazard Model in competing risk to model the achievement of HDI categories and identify factors that significantly influence HDI achievement in Indonesia. The data used is secondary data obtained from publications by the Central Statistics Agency for the observation period from 2014 to 2022. The results of the study show that the variables of HLS and Percentage of Poor Population have a significant effect on the achievement of the HDI category. The HLS variable has a positive effect (SHR > 1), while the Percentage of Poor Population has a negative effect (SHR < 1) on the achievement of the very high HDI category. Thus, increasing access to education and reducing poverty levels are important factors in accelerating the achievement of the HDI category in Indonesia.
Validasi dan Finalisasi Repositori File 06 Juli 2026_Kholif Basri
Keywords: Human Development Index; Competing Risk; Cumulative Incidence Function; Fine-Gray Subdistribution Hazard Model